Implementasi SAK ETAP pada Usaha Mikro, Kecil, dan Menengah (Studi pada Pertanian Sinar Tani Desa Waiheru) - Fatmawati, Fatmawati; Tomasoa, Theodora Florence; Dewi, Syahrina Noormala (Universitas Pattimura, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in regional economies, yet standardized financial reporting remains a major challenge. This study aims to analyze the implementation of SAK ETAP in the financial statements of Sinar Tani Agriculture in Waiheru Village. A qualitative descriptive method was applied, utilizing observation, in-depth interviews, and documentation with core members of the farmer group. The findings indicate that the financial statements have not fully adhered to SAK ETAP, especially in the absence of cash flow statements and notes to the financial statements, as well as inconsistencies in several balance sheet and income statement items. The conclusion emphasizes the need for a better understanding of SAK ETAP among agricultural MSMEs to foster transparency and accountability, ultimately facilitating access to formal financing. This in-depth analysis in the local agricultural context provides a fresh perspective on the practical challenges of accounting standard implementation. These results imply the necessity of ongoing training, intensive assistance, and collaboration with related institutions to ensure the effective and consistent application of SAK ETAP